Ratios!

Geometry Level pending

In A B C \triangle{ABC} , m C = 2 λ m\angle{C} = 2\lambda and z = C D z = \overline{CD} is the angle bisector of C \angle{C} .

Find: z ( a + b ) sin ( λ ) A A B C \dfrac{z(a + b)\sin(\lambda)}{A_{\triangle{ABC}}} .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

David Vreken
Feb 10, 2021

A A B C = A D B C + A A D C = 1 2 a z sin λ + 1 2 b z sin λ = 1 2 z ( a + b ) sin λ A_{\triangle ABC} = A_{\triangle DBC} + A_{\triangle ADC} = \frac{1}{2}az \sin \lambda + \frac{1}{2}bz \sin \lambda = \frac{1}{2}z(a + b)\sin \lambda , so z ( a + b ) sin λ A A B C = z ( a + b ) sin λ 1 2 z ( a + b ) sin λ = 2 \cfrac{z(a + b)\sin \lambda}{A_{\triangle ABC}} = \cfrac{z(a + b)\sin \lambda}{\frac{1}{2}z(a + b)\sin \lambda} = \boxed{2} .

Rocco Dalto
Feb 5, 2021

m C D B = 18 0 ( B + λ ) m\angle{CDB} = 180^{\circ} - (B + \lambda)

Applying the law of sines on A B C \triangle{ABC} \implies

b sin ( B ) = c sin ( 2 λ ) sin ( B ) = b sin ( 2 λ ) c \dfrac{b}{\sin(B)} = \dfrac{c}{\sin(2\lambda)} \implies \sin(B) = \dfrac{b\sin(2\lambda)}{c}

Appling the law of cosines on A B C c 2 = a 2 + b 2 2 a b cos ( 2 λ ) \triangle{ABC} \implies c^2 = a^2 + b^2 - 2ab\cos(2\lambda) \implies

sin ( B ) = b sin ( 2 λ ) a 2 + b 2 2 a b cos ( 2 λ ) \sin(B) = \dfrac{b\sin(2\lambda)}{\sqrt{a^2 + b^2 - 2ab\cos(2\lambda)}} \implies cos ( B ) = a b cos ( 2 λ ) a 2 + b 2 2 a b cos ( 2 λ ) \cos(B) = \dfrac{a - b\cos(2\lambda)}{\sqrt{a^2 + b^2 - 2ab\cos(2\lambda)}}

and applying the law of sines on B C D z sin ( B ) = a sin ( B + λ ) \triangle{BCD} \implies \dfrac{z}{\sin(B)} = \dfrac{a}{\sin(B + \lambda)} \implies

z = a sin ( B ) sin ( B ) cos ( λ ) + cos ( B ) sin ( λ ) z = \dfrac{a\sin(B)}{\sin(B)\cos(\lambda) + \cos(B)\sin(\lambda)}

Using the above

sin ( B ) = b sin ( 2 λ ) a 2 + b 2 2 a b cos ( 2 λ ) \sin(B) = \dfrac{b\sin(2\lambda)}{\sqrt{a^2 + b^2 - 2ab\cos(2\lambda)}}

and

cos ( B ) = a b cos ( 2 λ ) a 2 + b 2 2 a b cos ( 2 λ ) \cos(B) = \dfrac{a - b\cos(2\lambda)}{\sqrt{a^2 + b^2 - 2ab\cos(2\lambda)}}

and simplifying we obtain z = ( 2 a b a + b ) cos ( λ ) \boxed{z = (\dfrac{2ab}{a + b})\cos(\lambda)}

h = a sin ( B ) = a b sin ( 2 λ ) a 2 + b 2 2 a b cos ( 2 λ ) h = a\sin(B) = \dfrac{ab\sin(2\lambda)}{\sqrt{a^2 + b^2 - 2ab\cos(2\lambda)}} \implies A A B C = 1 2 a b sin ( 2 λ ) \boxed{A_{\triangle{ABC}} = \dfrac{1}{2}ab\sin(2\lambda)} \implies

z ( a + b ) sin ( λ ) A A B C = 2 \dfrac{z(a + b)\sin(\lambda)}{A_{\triangle{ABC}}} = \boxed{2} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...